Education and metabolic syndrome: a Mendelian randomization study - Liu, Dong; Xu, Zi-Xiang; Liu, Xue-lian; Yang, Hai-Ling; Wang, Ling-ling; Li, Yan (Frontiers in Nutrition, 2024)
The metabolic syndrome (MetS), a collection of conditions that heighten the risk of disease development and impose economic burdens on patients. However, the causal relationship between education and MetS was uncertain. In this study, the Mendelian randomization (MR) method was employed to elucidate the potential causal link between education and the MetS and its components.Method: single nucleotide polymorphisms (SNPs) associated with education, MetS, and its components were sourced from a public database, with the inverse varianceweighted (IVW) method utilized for analysis.Results: Education demonstrated a significant negative correlation with the risk of MetS (OR = 0.55, 95% CI = 0.48-0.63, P = 2.18E-51), waist circumference (OR = 0.80, 95% CI = 0.76-0.83, P = 4.98E-33), hypertension (OR = 0.96, 95% CI = 0.95-0.97; P = 4.54E-10), Fasting blood glucose (OR = 0.94, 95% CI = 0.91-0.97, P = 7.58E-6) and triglycerides (OR = 0.83, 95% CI := 0.79-0.87, P = 7.87E-18) while showing a positive association with high-density lipoprotein cholesterol (OR = 1.22, 95% CI = 1.18-1.25, P = 1.45E-31). Early intervention strategies are crucial for individuals with lower levels of education in effectively managing MetS and its related components.The findings of this study suggest that education can decrease the incidence of MetS. It is crucial to emphasize early intervention and diagnosis in individuals with lower levels of education.